Driver attitude and its influence on the energy waste of electric buses - Perrotta, Deborah (2014)
The objective of this paper is to analyze the influence of different driver behaviors on the energy consumption of electric buses. It shows that risk-taking attitudes on traffic are not only dangerous to the driver, to the bus users and to the surroundings, but also promotes a poorer performance of the vehicle itself, increasing its energy consumption and reducing the amount of energy that can be recovered on regenerative braking.